Central retinal vein occlusion in a young adult during risperidone therapy - (:unkn) unknown (My University, 2008)
BACKGROUND: Various articles in the literature point out the higher risk of venous thrombosis in patients taking antipsychotic drugs. However, to our knowledge, an association with central retinal vein occlusion (CRVO) has not been reported before. METHODS: We describe the clinical and angiographic findings of a patient with CRVO that may have been related to his antipsychotic medication. RESULTS: A 19-year-old patient had been taking risperidone and fluoxetine for the last 7 months. He presented with atypical nonischemic CRVO with atypical deep intraretinal hemorrhages, a swollen optic disk, dilatation and engorgement of retinal veins, and optic disk capillaries. Despite a detailed workup, no systemic or ocular risk factors for a thromboembolic event were found. He had hyperprolactinemia resulting from his medication. CONCLUSION: The use of risperidone may be a risk factor for CRVO.